Issues in conducting quantitative studies on the impact of coaching and mentoring in Higher Education - Jill Andreanoff (International Journal of Evidence Based Coaching and Mentoring, 2016)
Whilst there has long been a call for evidence of a more quantifiable nature to show the impact of coaching interventions, in particular within the education sector, there may be good reasons for why this has been absent thus far. This paper highlights the issues of conducting quantitative research to establish outcomes of coaching interventions. It explores peer coaching within an educational context and the use of a control group. The paper highlights the methodology used to conduct a quantitative study of a peer coaching intervention, comparing the academic attainment of a coached group of students with a group of students who received no coaching. Some findings are also discussed.